An Error Correction Model Analysis of Indonesia’s Tourism and International Trade - Hendratono, Tonny; Puspitasari, Veny Anindya (E-Journal of Tourism; Volume 5 Number 2 (September 2018)DO - 10.24922/eot.v5i2.42591, 2018)
The tourism sector is the mainstay of Indonesia's foreign exchange contributor. Through its affordability with various other sectors, tourism is considered to be able to influence the country's international trade through the mechanism of exports and imports. This study aims to analyze the influence of tourism on Indonesia's trade balance in the short and long term. The theory of comparative advantage and Heckscher-Ohlin are aimed to answer the purpose of this study. Using the Error Correction Model (ECM), this research shows that tourism has a positive and significant impact on exports and imports in the long and short term. However, in the long term the influence of tourism on imports is greater than that of exports. The opposite thing is happened in the short term. Keywords: tourism, international trade, Error Correction Model